Development and validation of an observational measure of symptoms of Reactive Attachment Disorder - Corval, R.; Belsky, J.; Baptista, J.; Mesquita, A.; Soares, I. (Attachment and Human Development, 2019)
Reactive Attachment Disorder (RAD) is presumed to be a consequence of social neglect and deprivation of the kind particularly associated with institutional care. Despite its clinical relevance there is a lack of assessment tools for RAD based on the direct observation of child–caregiver interaction. Here we describe the development and validation of such a tool for use with preschool children, the Rating of Inhibited Attachment Disordered Behavior (RInAB). The RInAB is composed of 17 ratings grouped in three subscales assessing (1) Attachment, (2) Exploratory, and (3) Socioemotional behavior. Participants were 134 institutionalized preschool children (M = 54.84 months; SD = 10.83; 60% boys) and their caregivers. Adequate reliability was found for RInAB subscales and total score. Confirmatory factor analyses documented the three aforementioned RInAB subscales. Correlational analyses documented: (i) construct validity via positive and significant associations with caregiver sensitivity and quality of child–caregiver relationship; (ii) convergence validity via association evidence with some emotionally/withdrawn inhibited items of the Disturbed Attachment Interview (DAI), as well as, with Child Behavior Checklist (CBCL)’s somatic complaints and withdraw syndrome scales; and (iii) discriminant validity via nonsignificant or negative associations with DAI-indiscriminate subscale, Rating of Infant and Stranger Engagement (RISE) and CBCL-externalizing problems. Discussion highlights the contributions complementary roles of RInAB for a comprehensive assessment of child RAD-related functioning.